Characterization and evaluation of commercial poly (vinylidene fluoride)‐g‐sulfonatedPolystyrene as proton exchange membrane. (28th June 2017) - Abdel‐Hady, E.E.; Abdel‐Hamed, M.O.; Awad, S.; Hmamm, M.F.M.
Abstract : The possibility of developing low‐cost commercial grafted and sulfonated Poly(vinylidene fluoride) (PVDF‐ g ‐PSSA) membranes as proton exchange membranes for fuel cell applications have been investigated. PVDF‐ g ‐PSSA membranes were systematically prepared and examined with the focus of understanding how the polymer microstructure (degree of grafting and sulfonation, ion‐exchange capacity, etc) affects their methanol permeability, water uptake, and proton conductivity. Fourier transform infrared spectroscopy was used to characterize the changes of the membrane's microstructure after grafting and sulfonation. The results showed that the PVDF‐ g ‐PSSA membranes exhibited good thermal stability and lower methanol permeability. The proton conductivity of PVDF‐ g ‐PSSA membranes was also measured by the electrochemical impedance spectroscopy method. It was found that the proton conductivity of PVDF‐ g ‐PSSA membranes depends on the degree of sulfonation. All the sulfonated membranes show high proton conductivity at 92°C, in the range of 27 to 235 mScm −1, which is much higher than that of Nafion212 (102 mScm −1 at 80°C). The results indicated that the PVDF‐ g ‐PSSA membranes are particularly promising membranes to be used as polymer electrolyte membranes due to their excellent stability, low methanol permeability, and high proton conductivity.